BIOSINTESIS DAN KARAKTERISASI PARTIKEL PERAK EKSTRAK TANAMAN DAUN PORANG (Amorphophallus muelleri Blume) SEBAGAI PENDETEKSI ION LOGAM MERKURI - Doni Notriawan; Febrika Laila; Eka Angasa; Gustria Ernis; Teja Dwi Sutanto; Reza Pertiwi; Ida Ayu Suci (Tanjungpura University, 2023)
This study aims to synthesize and characterize silver particles using Porang leaf extract (Amorphophallus muelleri Blume) and determine the selectivity of silver particles as mercury metal ion detectors. The study employed Porang leaf extract as a bioreductor and stabilizer, 0.01M AgNO3 solution as a precursor, and HgCl2 salt solution and PbCl2 salt solution as standard salt solutions to be tested for selectivity. The 2 g of Porang leaves used were cleaned, cut into pieces, allowed to stand at room temperature for three days, and mashed. Porang leaf powder was added with 50 mL of demineralized water and then heated for 15 minutes at a solution temperature of 80°C. The reaction of silver particle formation was carried out by adding Porang leaf extract and AgNO3 0.01M in variations of 1:3, 1:4, 1:5, 1:6, and 1:7, then irradiating under indirect sunlight for 15 minutes. The reaction results of a mixture of colloidal extract and AgNO3 solution showed a change in color to brownish-yellow. The color change indicated the formation of silver particles. The silver particles were then characterized with a UV-Vis spectrophotometer after 15 minutes of heating, 1 hour, and 5 hours at room temperature. The results obtained with colloidal silver particles can be synthesized with a bioreductor of Porang leaf extract (Amorphophallus muelleri Blume) with optimum variations of 1:3 and 1:4. The PSa results obtained in the mixture of silver particles formed were micro-nano-sized silver particles. The results of silver particles tested against metal ions showed that silver particles selectively detect Hg (II) metal ions in HgCl2 solutions compared to Pb (II) metal ions in PbCl2 solutions.